2022
DOI: 10.3389/fpubh.2022.1016169
|View full text |Cite|
|
Sign up to set email alerts
|

Detection of SARS-CoV-2 infection clusters: The useful combination of spatiotemporal clustering and genomic analyses

Abstract: BackgroundThe need for effective public health surveillance systems to track virus spread for targeted interventions was highlighted during the COVID-19 pandemic. It spurred an interest in the use of spatiotemporal clustering and genomic analyses to identify high-risk areas and track the spread of the SARS-CoV-2 virus. However, these two approaches are rarely combined in surveillance systems to complement each one's limitations; spatiotemporal clustering approaches usually consider only one source of virus tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…Our analyses included 41,672 positive SARS-CoV-2 RT-PCR tests from a total of 283,135 tests administered to 138,774 residents of the canton of Vaud (population 800,000), Switzerland, between March 2, 2020, and April 15, 2022. The testing procedure relied only on quantitative real-time PCRs and has been described in detail in previous studies ( 8 , 10 ). The study received approval from the Cantonal Research Ethics Commission of Vaud (CER-VD), Switzerland (n°2020-01302).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analyses included 41,672 positive SARS-CoV-2 RT-PCR tests from a total of 283,135 tests administered to 138,774 residents of the canton of Vaud (population 800,000), Switzerland, between March 2, 2020, and April 15, 2022. The testing procedure relied only on quantitative real-time PCRs and has been described in detail in previous studies ( 8 , 10 ). The study received approval from the Cantonal Research Ethics Commission of Vaud (CER-VD), Switzerland (n°2020-01302).…”
Section: Methodsmentioning
confidence: 99%
“…The SARS-CoV-2 pandemic has had a significant impact on the world's population and understanding the spatial and temporal patterns of its spread and its evolution is crucial for epidemic surveillance and control (1)(2)(3)(4)(5). Techniques such as hot-spot analysis, spatiotemporal clustering, and space-time scan statistics have been widely employed to analyze georeferenced data from SARS-CoV-2 RT-PCR testing (6)(7)(8)(9)(10)(11). These analyses have revealed that the incidence and the mortality of the disease are not evenly distributed but rather cluster in certain areas and peak at certain times, indicating a high degree of heterogeneity in the diffusion dynamics of the virus (12-14).…”
Section: Introductionmentioning
confidence: 99%
“…Our analyses included 41,672 positive SARS-CoV-2 RT-PCR tests from a total of 283,135 tests administered to 138,774 residents of the canton of Vaud (population 800,000), Switzerland, between March 2, 2020, and April 15, 2022. The testing procedure relied only on quantitative real-time PCRs and has been described in detail in previous studies (8,10). The study received approval from the Cantonal Research Ethics Commission of Vaud (CER-VD), Switzerland (n°2020-01302).…”
Section: Sars-cov-2 Rt-pcr Testing Datamentioning
confidence: 99%
“…The SARS-CoV-2 pandemic has had a significant impact on the world's population and understanding the spatial and temporal patterns of its spread and its evolution is crucial for epidemic surveillance and control (1)(2)(3)(4)(5). Techniques such as hot-spot analysis, spatiotemporal clustering, and space-time scan statistics have been widely employed to analyze georeferenced data from SARS-CoV-2 RT-PCR testing (6)(7)(8)(9)(10)(11). These analyses have revealed that the incidence and the mortality of the disease are not evenly distributed but rather cluster in certain areas and peak at certain times, indicating a high degree of heterogeneity in the diffusion dynamics of the virus (12-14).…”
Section: Introductionmentioning
confidence: 99%